2023
DOI: 10.3389/fphys.2023.1117666
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-intensity interval training as a suitable approach for offspring’s heart protection in rat: evidence from oxidative stress and mitochondrial genes

Abstract: Considerable scientific evidence suggests that the intrauterine environment plays a crucial role in determining the long-term health of offspring. The present study aims to investigate the effects of high-intensity interval training in maternal rats before and during pregnancy on the antioxidant status, mitochondrial gene expression, and anxiety-like behavior of their offspring. A total of thirty-two female rats were assigned to four maternal groups based on the timing of exercise: before pregnancy, before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…This indicated that the hepatic Nrf2 antioxidant systems of the AD mice were also in suppressed states, and treadmill exercise promoted Nrf2 phosphorylation and downstream antioxidant protein expression in the livers of the AD mice. Appropriate exercise could improve antioxidant capacity, and this was consistent with numerous recent studies [39][40][41]. Prooxidant and antioxidant levels in the livers of the AD mice were lower than those in normal mice, but there was oxidative damage, and treadmill exercise increased both the prooxidant and antioxidant levels but reduced oxidative stress, suggesting that treadmill exercise may have regulated the hepatic redox balances in the AD mice, ultimately reducing oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
“…This indicated that the hepatic Nrf2 antioxidant systems of the AD mice were also in suppressed states, and treadmill exercise promoted Nrf2 phosphorylation and downstream antioxidant protein expression in the livers of the AD mice. Appropriate exercise could improve antioxidant capacity, and this was consistent with numerous recent studies [39][40][41]. Prooxidant and antioxidant levels in the livers of the AD mice were lower than those in normal mice, but there was oxidative damage, and treadmill exercise increased both the prooxidant and antioxidant levels but reduced oxidative stress, suggesting that treadmill exercise may have regulated the hepatic redox balances in the AD mice, ultimately reducing oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
“…Most EV research has been conducted in nonpregnant populations; thus, current findings may not apply to our population of interest. Of the limited research examining EVs in the pregnant population, baseline levels of small EVs isolated from the plasma (10-120 nm) were higher in pregnant individuals than nonpregnant individuals (Mohammad, Hutchinson, et al, 2021). After a 30-min bout of moderate-intensity exercise, serum levels of small EVs were significantly higher in gesP than controls (Mohammad, Hutchinson, et al, 2021).…”
Section: Secreted Factorsmentioning
confidence: 94%
“…Of the limited research examining EVs in the pregnant population, baseline levels of small EVs isolated from the plasma (10-120 nm) were higher in pregnant individuals than nonpregnant individuals (Mohammad, Hutchinson, et al, 2021). After a 30-min bout of moderate-intensity exercise, serum levels of small EVs were significantly higher in gesP than controls (Mohammad, Hutchinson, et al, 2021). Conversely, levels of circulating large EVs, specifically endothelial and platelet EVs, were not impacted by an acute bout of walking, nor associated with markers of cardiorespiratory fitness (Abolbaghaei et al, 2023).…”
Section: Secreted Factorsmentioning
confidence: 97%
See 1 more Smart Citation